2021
DOI: 10.1002/vms3.611
|View full text |Cite
|
Sign up to set email alerts
|

Body temperatures of Manis pentadactyla and Manis javanica

Abstract: Body temperature is an important parameter for assessing animal health and physiological function. An iButton thermometer was used to measure the body temperatures of three Chinese pangolins (Manis pentadacyla) and three Sunda pangolins (M. javanica).The body temperature of Chinese pangolins was 33.2 ± 0.95 • C (30.6-34.2 • C, n = 3) and that of Sunda pangolins was 32.8 ± 0.48 • C (31.7-34.2 • C, n = 3). The daily variation in body temperature was 1.0-2.9 • C in three Chinese pangolins and 1.2-1.9 • C in three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
2
2
Order By: Relevance
“…Pangolins in our study, however, had mean body temperatures that were higher compared with those measured previously for Temminck’s pangolins in captivity (32–34°C; Boyles et al, 2019 ; Wicker et al, 2020 ) and for one animal in the wild (32–35°C; Pietersen, 2013 ). The highest (absolute maximum) body temperature (38.2°C) we measured was higher than the maximum body temperatures reported previously for any pangolin species in captivity (33.9–37.8°C, Jones, 1973 ; McNab, 1984 ; Heath and Hammel , 1986 ; Heath, 1987 ; Boyles et al, 2019 ; Challender et al, 2020 ; Yu et al, 2021 ) and almost 3°C higher than that previously reported for a wild Temminck’s pangolin (35.4°C), measured across 34 days in winter ( Pietersen, 2013 ). The lowest body temperature recorded for a pangolin in our study (28.9°C in March 2016) was within the range of minimum body temperatures recorded previously for captive animals (~27.6–33.4°C; McNab, 1984 ; Heath and Hammel, 1986 ; Heath, 1987 ; Yu et al, 2021 ) and similar to that recorded for a wild pangolin (29.5°C; Pietersen, 2013 ).…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Pangolins in our study, however, had mean body temperatures that were higher compared with those measured previously for Temminck’s pangolins in captivity (32–34°C; Boyles et al, 2019 ; Wicker et al, 2020 ) and for one animal in the wild (32–35°C; Pietersen, 2013 ). The highest (absolute maximum) body temperature (38.2°C) we measured was higher than the maximum body temperatures reported previously for any pangolin species in captivity (33.9–37.8°C, Jones, 1973 ; McNab, 1984 ; Heath and Hammel , 1986 ; Heath, 1987 ; Boyles et al, 2019 ; Challender et al, 2020 ; Yu et al, 2021 ) and almost 3°C higher than that previously reported for a wild Temminck’s pangolin (35.4°C), measured across 34 days in winter ( Pietersen, 2013 ). The lowest body temperature recorded for a pangolin in our study (28.9°C in March 2016) was within the range of minimum body temperatures recorded previously for captive animals (~27.6–33.4°C; McNab, 1984 ; Heath and Hammel, 1986 ; Heath, 1987 ; Yu et al, 2021 ) and similar to that recorded for a wild pangolin (29.5°C; Pietersen, 2013 ).…”
Section: Discussioncontrasting
confidence: 74%
“…The highest (absolute maximum) body temperature (38.2°C) we measured was higher than the maximum body temperatures reported previously for any pangolin species in captivity (33.9–37.8°C, Jones, 1973 ; McNab, 1984 ; Heath and Hammel , 1986 ; Heath, 1987 ; Boyles et al, 2019 ; Challender et al, 2020 ; Yu et al, 2021 ) and almost 3°C higher than that previously reported for a wild Temminck’s pangolin (35.4°C), measured across 34 days in winter ( Pietersen, 2013 ). The lowest body temperature recorded for a pangolin in our study (28.9°C in March 2016) was within the range of minimum body temperatures recorded previously for captive animals (~27.6–33.4°C; McNab, 1984 ; Heath and Hammel, 1986 ; Heath, 1987 ; Yu et al, 2021 ) and similar to that recorded for a wild pangolin (29.5°C; Pietersen, 2013 ). Although data on the body temperature of pangolins in captivity are useful for understanding pangolin physiology, the data likely do not accurately reflect the body temperature patterns of wild pangolins exposed to natural conditions.…”
Section: Discussioncontrasting
confidence: 74%
“…Instead, it may be more appropriate to correct the temperature detected by the blood gas analyzer for the body temperature of the measured animal. Pangolins have a lower body temperature than most mammals [ 43 , 44 ]. When detecting blood gases in the pangolin, the test results were corrected by temperature to make the test values more representative.…”
Section: Discussionmentioning
confidence: 99%
“…The thermistor probe was placed approximately 3 cm into the rectum to measure the pangolin’s rectal temperature (Mindray, uMEC12Vet, monitor, ShenZhen, China). The body temperature of the pangolin was 33.0 ~ 33.8℃during anaesthesia (the physiologic rectal temperature: 32.2 ~ 35.2℃) [ 11 , 12 ]. On preliminary gross examination, in the center of the left wound, there was a 2 cm diameter scab (Fig.…”
Section: Case Reportmentioning
confidence: 99%